Trickle-Bed Laboratory Reactorsf or Kinetic Studies - Mary, Gaetan; Chaouki, Jamal; Luck, Francis
In this paper, different phenomena affecting laboratory trickle-bed reactors are carefully reviewed. Before focusing on laboratory scale, some general considerations about trickle-bed reactors are discussed: regimes, industrial uses, etc. The main factors a laboratory trickle bed reactors are presented and detailed. The greatest six factors include: homogeneity of the catalyst bed, catalyst wetting, axial dispersion, channeling, isothermicity and mass transfer. These factors are reviewed and different criteria, suggested in the literature, are given in order to minimize the influence of these six factors; for each criterion, a simple application is presented. Finally, the application of all the criteria given in the paper is based on a hypothetical example (hydrodesulfurization).
Keywords: TRICKLE-BED REACTORS; LABORATORY SCALE; PLUG FLOW REACTORS; CATALYST; WETTING; AXIAL DISPERSION; MASS TRANSFER; ISOTHERMICITY; CHANNELING; HOMOGENEITY; BED OF CATALYST